Critical competency attributes of Technical and Vocational Education and Training (TVET) postgraduate students in online learning environment - Omar, Muhd Khaizer; Ding, Meng Jie; Mohd Puad, Mohd Hazwan; Ismail, Normala (Human Resource Management Academic Research Society, 2021)
Student competency has become the central agenda in graduates' employability. Reflecting on the overarching situation of COVID-19 pandemic, students have been compelled to acquire knowledge using online platforms, conjecturing the competency attributes being left out from conventional teaching and learning environments. This paper examines the development of competency attributes: knowledge, skills, and attitudes, which were selected as main variables. A correlation analysis was performed to obtain the results of the relationship between the competency attributes and the online learning environment. There were 70 postgraduate students, randomly selected as samples of the study. The discussion of the results centered on the competency attributes developed by the students and their relationships with the online learning environment. The implications for educational stakeholders based on the findings are further discussed.